2018
DOI: 10.1038/s41375-018-0257-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics and gene mutations influence survival in older patients with acute myeloid leukemia treated with azacitidine or conventional care

Abstract: Older patients with newly diagnosed acute myeloid leukemia (AML) in the phase 3 AZA-AML-001 study were evaluated at entry for cytogenetic abnormalities, and a subgroup of patients was assessed for gene mutations. Patients received azacitidine 75 mg/m2/day x7 days (n = 240) or conventional care regimens (CCR; n = 245): intensive chemotherapy, low-dose cytarabine, or best supportive care only. Overall survival (OS) was assessed for patients with common (occurring in ≥10% of patients) cytogenetic abnormalities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 42 publications
5
106
0
1
Order By: Relevance
“…Treatment of patients with TP53-mutated AML remains challenging. Non-intensive therapies with hypomethylating agents-azacitidine and decitabine-are frequently offered, especially to elderly patients [48,49]. These drugs show acceptable response rates and favorable toxicity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of patients with TP53-mutated AML remains challenging. Non-intensive therapies with hypomethylating agents-azacitidine and decitabine-are frequently offered, especially to elderly patients [48,49]. These drugs show acceptable response rates and favorable toxicity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Median number of cycle was 10 (range 3-15). Median OS was 15 months (range, [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Correlation Between Aza Response and Putative Function Of mentioning
confidence: 99%
“…11,12 Response rates for AZA treatment of t-MN are similar to de novo MDS but were associated with shorter survival. [13][14][15][16] The genetic landscape of MDS/AML has been extensively studied with driver mutations involving transcription factors, signal transduction proteins, epigenetic modifiers, and components of RNA splicing. [17][18][19] Notably, the molecular architecture in patients with therapy-related disease is distinct from de novo myeloid neoplasms.…”
mentioning
confidence: 99%
“…A subgroup analysis of the AZA-001 trial focusing on low-blast count AML [19], and a large randomized phase III trial in elderly AML patients with bone marrow blast counts > 30% showed that AZA improved survival compared to conventional care in older AML patients deemed ineligible for intensive chemotherapy [20]. The survival benefit was particularly apparent in high-risk subgroups with adverse cytogenetics or myelodysplasia-related changes [21]. DAC showed activity in older patients with poor/intermediate risk, but failed to improve survival when compared to best supportive care or low-dose AraC [22].…”
Section: In Acute Myeloid Leukemiamentioning
confidence: 99%